A Descriptive Study to Determine the Effect of Use of New Social Media Channels in Political Marketing Communications on Generation Z: The Example of Youtube and Twitch - Aktepe, Hilal Saadet; Durukan, Tülin (Journal of Applied And Theoretical Social Sciences, 2022)
The fact that social media has become one of the main communication tools, especially for the Z generation, has made the use of this tool in marketing communication widespread. Although the use of social media as a political marketing tool has a close history for our country, it has taken its place in a strategic position for the upcoming 2023 elections. This election has a special and critical meaning for the parties as it is the first election for the Z generation born after 1996 to vote. As a matter of fact, the social networks-like structure, which is expressed by Kotler with the concept of "netizenship" in the communication between consumers in product and service marketing, has started to exist with the networks established in political marketing of political parties and leaders. This structure has spread rapidly during the Covid 19 pandemic and has begun to spread to the community base, exceeding the boundaries of the Z generation. Twitch live broadcasts, which started broadcasting as an online gaming platform with Youtube live broadcasts during online communication pandemic process, have been the channels that political leaders in our country directly reach, especially to the Z generation. Online broadcasts have advanced in a different way in reaching the masses with traditional media. Within the scope of this study, the social media interactions of Turkish politicians who broadcast on Youtube and Twitch in the years 2020-2021 will be examined and the importance of these new channels in political marketing will be emphasized.